2017
DOI: 10.21037/atm.2017.07.10
|View full text |Cite
|
Sign up to set email alerts
|

Circulating DNA in EGFR-mutated lung cancer

Abstract: Circulating tumor DNA (ctDNA) consists of short double stranded DNA fragments that are released by tumors including non-small cell lung cancer (NSCLC). With the identification of driver mutations in the epidermal growth factor receptor (EGFR) gene and development of targeted tyrosine kinase inhibitors (TKIs), the clinical outcome of NSCLC patients in this subgroup has improved tremendously.The gold standard to assess EGFR mutation is through tissue biopsy, which can be limited by difficulty in accessing the tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 55 publications
1
23
0
Order By: Relevance
“…Studies have shown that ctDNA analysis is able to detect driver EGFR mutations in patients' plasma with high sensitivity and specificity, correlating with clinical outcomes including ORR, PFS, and OS . In September 2014, the European Medicines Agency (EMA) recommended the use of plasma ctDNA for genotyping in cases where tissue sample was not available.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have shown that ctDNA analysis is able to detect driver EGFR mutations in patients' plasma with high sensitivity and specificity, correlating with clinical outcomes including ORR, PFS, and OS . In September 2014, the European Medicines Agency (EMA) recommended the use of plasma ctDNA for genotyping in cases where tissue sample was not available.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that ctDNA analysis is able to detect driver EGFR mutations in patients' plasma with high sensitivity and specificity, correlating with clinical outcomes including ORR, PFS, and OS. 4,10,11 In September 2014, the European Medicines Agency (EMA) recommended the use of plasma ctDNA for genotyping in cases where tissue sample was not available. The US Food and Drug Administration (FDA) approved the cobas ® EGFR Mutation Test v2 to detect the presence of specific NSCLC mutations (exon 19 deletion or exon 21 [L858R] substitution) in patients' blood to determine who would be candidates for treatment with erlotinib, as well as to detect patients with T790M mutations who would benefit from osimertinib.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The last section focuses on the rapid introduction of blood-based biomarker testing into routine practice with Velcheti et al (8) providing a general review of the available and emerging technology for ctDNA and CTCbased approaches. Next, Singh et al (9) will review the already carefully validated use of ctDNA testing for upfront EGFR mutation and EGFR T790M detection. Lastly, Marmarelis et al (10) will explore the large diversity of up and coming opportunities for ctDNA utilization in the clinic to optimize patient care.…”
Section: Emerging Uses Of Biomarkers In Lung Cancer Managementmentioning
confidence: 99%